Development of fungal sterol biosynthesis inhibitors as new drug leads for the treatment of Chagas disease - Smith, Erin Nicole (Curtin University, 2014)
Pyrifenox is a potential drug candidate for the treatment of Chagas disease. A new modular synthesis was established to make pyrifenox and its analogues. These analogues lead to the discovery of compounds that inhibited the causative parasite, Trypanosoma cruzi, at the nanomolar range and the discovery of a new class of compound for the potential treatment of Chagas disease